GEOGRAPHIC INFORMATION SYSTEM FOR ZONATION MAPPING OF STATE JUNIOR HIGH SCHOOL, SURABAYA CITY - Agustina, Rima; Thoyibah, Nurut; Falani, Achmad Zakki (Universitas Islam Negeri Raden Intan Lampung, 2022)
The zoning is a New Student Acceptance System (PPDB) which is enforced by determining the zone radius by the respective regional government, and schools are required to accept a prospective student who is domiciled in the closest radius zone with a certain percentage of the total number of student to be accepted. To create an equal distribution of quality education in all schools in Indonesia. To find out the zoning of schools in the area, you can use the Geographic Information System (GIS) in the zoning mapping process, especially at (SMPN) in Surabaya City to find out the zoning area easily and accurately, whichever is closest to their domicile. By utilizing GIS, it is hoped that will facilitate the presentation of information, especially those related to school zoning. To find the maximum zoning distance for SMPN Surabaya, the author uses buffering method. Implementation of the GIS program for zoning mapping for SMPN Surabaya in the form is running well. This system can display information and location regarding the Negen Middle School in Surabaya using the buffering method, in addition, this system can also display the display in kilometres and the location of the prospective student to the destination Negen Middle School. The result of testing the system through the black box shows that the zoning information system at SMPN is feasible to use.